Anti-aromatic carbon ring engineered graphyne nanostructures for high-performance water electrolysis - Cuimei Li; Dong Cao; Dandan Guo; Changxiang Guo; Chun-Ran Chang (Chemical Engineering Journal, 2026)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Dopant-Enhanced harmonization of α-Fe2O3 oxygen migration and surface catalytic reactions during chemical looping reforming of methane - Hui-Xin Zhang; Xi-Yang Yu; Xue Su; Xin Gao; Zheng-Qing Huang; Bolun Yang; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Ionic liquids bonded in mesoporous HAP serve as efficient catalysts for CO2 fixation - Decun Luo; Zhen-Yu Zhang; Hao Yuan; Xi-Yang Yu; Xin Gao; Zhun Hu; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

Characteristics of root growth and sugar translocation in yellowing symptom of melon - Hee Ju Lee; Sang Gyu Lee; Chang Sun Choi; Won Byoung Chae; Kyung Ran Do; Changhoo Chun (Horticulture, Environment, and Biotechnology, 2015)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Neurodevelopment of Infants with Prenatal Exposure to Polybrominated Diphenyl Ethers - Cherng-Gueih Shy; Huei-Lin Huang; Gou-Ping Chang-Chien; How-Ran Chao; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)